Faktor - Faktor yang Berhubungan dengan Pelaksanaan Triase - Gervasius Nong Sensi; Yanny Trisyani W; Aan Nuraeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine what factors influence the implementation of triage in the Emergency Unit. This research method uses a literature review conducted with PRISMA guidance and electronic databases, namely Google Scholar, Pubmed, and Science Direct, with the keywords